The use of cooperative learning in economics in the further education and training phase in the Free State Province - Van Wyk, Micheal Moos (University of the Free State, 2007)
In recent years, South African teachers were compelled to make an important paradigm shift in education from a teacher-centred approach to a learner-centred approach. Put differently, the emphasis is now on an outcomes-based education (OBE) approach as the key underlying principle of the National Curriculum Statements (NCS). Furthermore this paradigm shift in teaching and learning emphasized an active participation of learners which necessitated Economic teachers to restructure their teaching strategies in terms of the NCS. The purpose of this study was to design a framework for the implementation of cooperative learning as a teaching strategy for Economics teachers in the Further Education and Training (FET) phase in Free State secondary schools. A literature study and an empirical research was conducted for structuring of such a framework with different components in the design and implementation of cooperative learning as a teaching strategy for Economics teachers. To achieve the aforementioned, OBE in general was outlined. Secondly, the elements, principles, different OBE curriculum models were discussed. Thirdly, problem areas and arguments in defence of the implementation thereof in South African schools were explained. Fourthly, a multi paradigm perspective on the OBE approach, the National Qualifications Framework (NQF) and the place of the NCS for the FET phase were interrogated from an OBE curriculum model point of view. Furthermore Economics as a social science was compared to other sciences and models of economic teaching. Economics as a school subject and the interrelated components to the curriculum were broadly explained. As reinforcement to the previous mentioned aspects, a historical development as well as viewpoints on cooperative learning were outlined. Subsequently the importance of cooperative learning models, strategies, and group compositions were thoroughly analysed. In conclusion, the perspective on the development of cooperative learning, the rationale thereof, as well as the advantages and disadvantages were scrutinized. Emanating from the literature review an empirical study was conducted to determine the current status of in-service training amongst Economic teachers and to which extent they apply cooperative learning techniques. Economic teachers and Learning facilitators acted as respondents for obtaining data that was used for the design of a framework for implementation of cooperative learning. Findings of the responses of the questionnaires revealed that there was a great need for more in-service training especially for both beginner and experienced teachers. Furthermore the majority of respondents indicated a deficiency in the application of cooperative learning in their Economic classes. Thereafter a number of recommendations were made regarding the in-service training and the effective application of cooperative learning as a teaching strategy in Economics teaching. In summation, the literature study, the findings of the empirical research and recommendations of this study forms the basis for the design of a framework for the implementation of cooperative learning as a teaching strategy for Economics teachers in the Further Education and Training (FET) phase.

In onlangse jare, is Suid-Afrikaanse onderwysers genoodsaak om ‘n belangrike paradigmaskuif in die onderwys te maak vanaf ‘n onderwysergesentreerde na ’n leerdergesentreerde benadering. Die klemverskuiwing as fokus is nou gerig op ’n uitkomsgerigte onderwysbenadering (UGO-benadering) as belangrike onderliggende beginsel van die Nasionale Kurrikulumverklaring (NKV). Verder noodsaak hierdie paradigmaskuif in onderrig en leer ‘n aktiewe deelname van leerders waarbinne Ekonomie-onderwysers hul onderrigstrategieë herstruktureer in terme van die NKV. Die doel met hierdie studie is om ‘n raamwerk vir die implementering van koöperatiewe leer as ‘n onderrigstrategie vir Ekonomie-onderwysers in die Verdere Onderwys- en Opleidingfase (VOO-fase) in Vrystaatse sekondêre skole te ontwerp. ‘n Literatuurstudie en ‘n empiriese navorsing is uitgevoer vir die strukturering van so ‘n raamwerk met verskillende komponente in die ontwerp en implementering van koöperatiewe leer as ‘n onderrigstrategie vir Ekonomie-onderwysers. Om die voorafgaande te bereik, is uitkomsgerigte-onderwys (UGO) in die algemeen uitgelig. Tweedens is die elemente, beginsels en verskillende UGOkurrikulummodelle verduidelik. Derdens is probleemareas en argumente ter verdediging van die implementering daarvan in Suid-Afrikaanse skole verduidelik. Vierdens is ‘n multiparadigma-perspektief op die UGO-benadering, die Nasionale Kwalifikasieraamwerk (NKR) en die plek van die NKV vir die VOO fase vanuit ‘n UGO-kurrikulummodel in perspektief gestel. Verder is Ekonomie as sosiale wetenskap vergelyk met ander wetenskappe en modelle van ekonomiese onderrig. Ekonomie as skoolvak en die verwante komponente tot die kurrikulum is breedvoerig bespreek. As versterking tot die voorafgaande apsekte is ‘n historiese ontwikkeling sowel as die beskouings van koöperatiewe leer uitgelig. Daaropvolgens is die belangrike koöperatiewe leermodelle, strategieë asook groepsamestellings volledig ontleed. In die samevatting is die perspektief op die ontwikkeling van koöperatiewe leer, die rasionaal daarvan, asook die voor- en nadele noukeurig ondersoek. Voorspruitend uit die literatuurstudie is ‘n empiriese studie uitgevoer om te bepaal wat die huidige stand van indiensopleiding van Ekonomie-onderwysers is en tot watter mate hul koöperatiewe leer toepas. Ekonomie-onderwysers en leerfasiliteerders het opgetree as respondente vir die verkryging van inligting wat gebruik is vir die ontwerp van ‘n raamwerk vir die implementering van koöperatiewe leer. Bevindinge van response van die vraelyste het aangedui dat daar ‘n groot behoefte vir meer indiensopleiding veral vir beide beginner- en ervare onderwysers bestaan. Verder het die meerderheid respondente aangetoon dat hulle onbevoeg is om koöperatiewe leer in hul Ekonomieklasse toe te pas. Daarna is ‘n aantal aanbevelings ten opsigte van indiensopleiding en die toepassing van koöperatiewe leer as ‘n onderrigstrategie in Ekonomie geformuleer. Opsommend vorm die literatuurstudie, die bevindinge van die empiriese navorsing en aanbevelings van hierdie studie die basis vir die ontwerp van ‘n raamwerk vir die implementering van koöperatiewe leer as ‘n onderrigstrategie vir Ekonomie-onderwysers in die VOO-fase.
Thesis (Ph.D. (Curriculum Studies))--University of the Free State, 2007
Keywords: Economics -- Study and teaching (Secondary); Competency-based education -- South Africa -- Free State; Group work in education.; Further Education and Training phase; Economics learning facilitators; Framework; Free State Province; Free State Department of Education; National Curriculum Statement for Economics; Outcomes-Based Education; Teaching strategy; Training needs; Economic and Management Sciences; Economics; Cooperative learning; National qualifications framework